1991
DOI: 10.1177/019459989110500518
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Triton Tumor of the Head and Neck

Abstract: Malignant triton tumor is a rare, usually aggressive sarcoma consisting of a malignant schwannoma with rhabdomyoblastic differentiation. Although 20% of cases are located in the head and neck, this unusual tumor has not-to our knowledge-been described in the otolaryngology literature. We present the tenth reported case of triton tumor of the head and neck and the second involving the paranasal sinuses.'-9 An analysis of head and neck triton tumors suggests a possible subset of patients with lower-grade histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 8 publications
2
22
1
Order By: Relevance
“…4,5 One of these cases showed welldifferentiated histology and low mitotic activity 5 ; the other case was also low-grade sarcoma with a high degree of skeletal differentiation with focal cytological atypia without necrosis or significant mitotic activity. 4 Our case also showed moderate cellular pleomorphism and low mitotic activity. These findings are unlike those of MTT in other sites, which are histologically high-grade with large numbers of mitoses.…”
Section: à17mentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 One of these cases showed welldifferentiated histology and low mitotic activity 5 ; the other case was also low-grade sarcoma with a high degree of skeletal differentiation with focal cytological atypia without necrosis or significant mitotic activity. 4 Our case also showed moderate cellular pleomorphism and low mitotic activity. These findings are unlike those of MTT in other sites, which are histologically high-grade with large numbers of mitoses.…”
Section: à17mentioning
confidence: 99%
“…3 It shows rapid growth, early metastasis and poor prognosis. 4 The tumor was first described by Masson 5 in 1932. A review of the literature yielded 48 reported cases, and only 10 cases of MTT of head and neck have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only two patients had died at the time of manuscript publication, one from an unrelated malignancy with no evidence of MTT recurrence, and the other a patient who had non-resectable tumor at initial presentation. All other patients were treated surgically, with eight receiving adjuvant radiotherapy and two adjuvant chemotherapy as summarized in Table 1 [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[26] The majority of malignant Triton tumors occur in the setting of NF1, and as a result, the affected patient is typically young [22,23]. About a third of malignant Triton tumors affect the head and neck where they can involve virtually any anatomic subsite [27][28][29]. The rhabdomyoblasts in malignant Triton tumors are typically focal, and they often stand out at low power as their abundant eosinophilic cytoplasm is distinctly different than the pale background Schwannian cells (Fig.…”
Section: Malignant Triton Tumormentioning
confidence: 99%